(untitled) (Theatrum historiae, 2012)
The article investigates the some research approaches to the role of the sanctity and the saintly models in the medieval society. First of all the problem of interaction between the saint (male or female) and its social background (confessors, regular order, friends and relatives, social and ecclesiastic hierarchy) has to be faced, as well as the historical context, which the sources were originating from. The hagiography and other „official“ documents as well as the letters are able to provoke the questions not only on the character of the saintly model, but also on its function in the society at that time, on the interest of those, who seek to procure the canonization, and on their policy in that trial. This article works with the example of the 14th century saint, Caterina da Siena.